The Effect of Make up Rating Content on Purchasing Decisions in E-commerce - Riskian, Elsa Hasna (International Journal Administration, Business & Organization, 2023)
This study was conducted to see whether there is an influence of make up rating content on the purchasing decisions of Bandung State Polytechnic students, Indonesia in e-commerce. The sample used in the study were 103 respondents who are students of Bandung State Polytechnic, Indonesia who have used and bought make up in e-commerce and often see make up product rating content on social media. The method used in this research is descriptive analysis, data analysis using correlation and regression. Data collection is used through google forms that are distributed directly to respondents who match the criteria through social media. The results of this study indicate that the content rating of make up products has a significant effect on purchasing decisions by 64.1%. While the remaining 35.9% is influenced by other factors.